(untitled) (Análisis Económico, 2018)
Se estimó un modelo econométrico para el consumo de la energía eléctrica en el municipio de San Juan del Río, Queretaro, y determinar qué variables lo afectan. Para realizar dicha estimación se usó información estadística mensual comprendiendo el periodo enero de 2003 a mayo de 2010. La elasticidad precio propia obtenida en el corto y largo plazo fue de -0.6943 y -2.2616, lo que corresponde a un servicio inelástico y elástico, respectivamente. La elasticidad ingreso de la demanda en el corto y largo plazo fue de 0.4320 (servicio normal necesario) y 1.4073 (servicio normal de lujo). Clasificación JEL: C51 Abstract These days, domestic electricity consumption for diverse activities is of an enormous importance. The lack of it can, generally speaking, produce social and family instability. Thus it is convenient that decision making be based upon the results of demand elasticities, evaluating proposals (and their effects), before being approved. An econometric model for the consumption of electrical energy in the municipal area of San Juan del Río is estimated, as also the variables that affect it. In order to carry out the estimation, monthly statistical information was used, covering the period January of 2003-May of 2010. The proper price elasticities obtained during the short, and long term, were -0.69 and -2.26 respectively, which correspond to an inelastic and elastic service respectively. The income elasticities of demand during the short and long terms were 0.43 (necessary normal service) and 1.41 (normal luxury service) respectively.